2023
DOI: 10.3390/ani14010142
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Imaging as a Method to Indirectly Assess Peripheral Vascular Integrity and Tissue Viability in Veterinary Medicine: Animal Models and Clinical Applications

Daniel Mota-Rojas,
Asahi Ogi,
Dina Villanueva-García
et al.

Abstract: Infrared thermography (IRT) is a technique that indirectly assesses peripheral blood circulation and its resulting amount of radiated heat. Due to these properties, thermal imaging is currently applied in human medicine to noninvasively evaluate peripheral vascular disorders such as thrombosis, thromboembolisms, and other ischemic processes. Moreover, tissular damage (e.g., burn injuries) also causes microvasculature compromise. Therefore, thermography can be applied to determine the degree of damage according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…A total of 94 references were cited in this review. This methodology was also adopted in the study by Mota-Rojas et al [18] and Camargo-Júnior et al [19].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 94 references were cited in this review. This methodology was also adopted in the study by Mota-Rojas et al [18] and Camargo-Júnior et al [19].…”
Section: Methodsmentioning
confidence: 99%
“…Some controlled experimental studies in rodents have reported that the alteration of controlled tissue perfusion causes a significant decrease in surface temperature in the affected tissue [ 72 , 73 , 74 ]. This has suggested that IRT could be used as a tool for evaluating the superficial thermal response to monitor wounds or injuries requiring treatment, such as flaps or tissue graft techniques [ 16 ]. This was reported in a clinical study of 16 cats (healthy cats = 10 and sick cats = 6).…”
Section: Infrared Thermal Monitoring During Rehabilitation Techniquesmentioning
confidence: 99%
“…After tissue damage, proinflammatory mediators are released, causing the vasodilation of capillaries, venules, or arterioles, with a subsequent increase in local temperature [ 13 , 14 , 15 ]. On the other hand, local hypothermia can be seen in patients with vascular compromise and ischemia issues [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the technologies used to investigate animal comfort and environmental conditions quickly, non-invasively and with reliable and replicable results, monitoring using near-infrared thermography has been gaining ground, with applications in different areas of scientific knowledge, such as early diagnosis of diseases, non-invasive assessment of rectal temperature, determination of animal thermal stress and thermal characterization of the environment in which they live [ 23 , 24 ]. The radiometric imaging allow data to be obtained by evaluating targets such as the surface of animals and correlating them with the production systems studied [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%